Mindfulness Training as Stress Prevention for Guidance and Counseling Teachers During a Pandemic - Wibowo, Mungin Eddy; Febrianti, Thrisia; Aliyah, Urotul; Naini, Rohmatus (HM Publisher, 2022)
The purpose of this service activity is to improve the competence of guidance and counseling teachers through group counseling training with mindfulness training. The method used in this service is the method of reflection, group discussion, and simulation. The target to be achieved from the BK teacher is a change in attitude or behavior in developing self-potential to carry out and conduct training for yourself as well as application to counselees on various problems, such as stress with mindfulness training. The results of these activities participants felt a significant impact on themselves both physically, such as feeling less tired, headaches and psychologically feeling comfortable, relieved, and calm.